Learner-centered teaching in a Higher Education course: a case study with a recognized researcher in Sports Coaching (Research, Society and Development, 2021)
Sport coaching researchers have provided generous recommendations on the importance of developing coach education programs based on learner-centered teaching (LCT) principles. However, empirical studies are rare, and without concrete examples, administrators and instructors will be reluctant to adopt this approach. In this case study, we used Weimer’s (2002, 2013) five dimensions of LCT to analyze (a) the perspective of a recognized researcher in the LCT coach development field, (b) his course plan and delivery strategy, and (c) the students’ perceptions of this course. A qualitative approach was used and included different tools to collect the data. The first two authors attended all the lessons, participated in all the learning activities, and took notes in a reflective journal. At the end of the semester, they conducted a semi-structured interview to get the instructor’s perspective on the LCT approach. Finally, an e-mail was sent to the students to collect their perceptions. The data were analyzed and interpreted using concept mapping, and Weimer’s five dimensions. The results showed that (a) most of the LCT dimensions were respected in the planning and delivery of the course, (b) there were times when the instructor felt uncomfortable playing a less important role, and (c) most students had positive learning experiences, although some have been taken out of their comfort zone with this new teaching approach. The article ends with a reflection on the recent impact of COVID-19 on education in Higher Education (HE).